Genetic correlations in the dental dimensions of Saguinus fuscicollis. Issue 3 (24th May 2019) - Hardin, Anna M.
Abstract: Objectives: The objectives of this study are to describe genetic correlations between dental dimensions in a platyrrhine primate, to assess whether the brown‐mantled tamarin dentition exhibits genetic modularity by tooth type, and to discuss the relationship between body size reduction and the genetic architecture of dental traits. Materials and methods: Genetic correlations were estimated for linear dental measurements, estimated crown areas, and measures of relative premolar and molar size from 302 individuals, using a pedigree of 386 individuals, with maximum likelihood variance decomposition in SOLAR. Results: Genetic correlation estimates indicate strong genetic integration in the dentition of brown‐mantled tamarins, with little evidence of modularity by tooth type, within and between the maxilla and mandible. The relative molar size variable hypothesized to be genetically patterned in baboons is not significantly heritable, and relative premolar size does not meet the criteria to be considered genetically patterned in this population. Discussion: These results demonstrate variation in the pattern of genetic correlations between dental dimensions in primates, providing evidence of evolution of the genetic architecture in the callitrichine lineage. Genetic integration of dental dimensions without modularity by tooth type, as demonstrated here, is expected to constrain dental evolution in ways that modularity would not. The role of body size reduction in the callitrichine lineage in the evolution of the genetic architecture of the dentition is discussed. Quantitative genetic analyses of dental dimensions in more primate populations will provide greater evidence of variation and evolution in the genetic architecture underlying primate dental morphology.